Deciphering the role of host species for two Mycobacterium bovis genotypes from the European 3 clonal complex circulation within a cattle‐badger‐wild boar multihost system. Issue 1 (15th December 2022) - Canini, Laetitia; Modenesi, Gabriela; Courcoul, Aurélie; Boschiroli, Maria‐Laura; Durand, Benoit; Michelet, Lorraine
Abstract: Bovine tuberculosis is a common disease affecting cattle and wildlife worldwide. Mycobacterium bovis circulation in wildlife decreases the efficacy of surveillance and control programs in cattle. Strains of the European 3 clonal complex are the most frequent in France. The aim of our work was hence to investigate the role played by cattle and wildlife species in the circulation of two M. bovis European 3 strains circulation. WGS of M. bovis strains collected between 2010 and 2017 in two distinct areas (Nouvelle‐Aquitaine region, NAq, and Côte‐d'Or département, CdO), from badgers, wild boars, and cattle were used in an evolutionary model to infer the transition between the three species. We computed host species transition and persistence between two consecutive nodes and the average number of transitions per tree. In total, 144 and 218 samples were collected respectively in CdO and NAq. In CdO, three between‐species transition rates stood out: from cattle to badgers, from badgers to wild boars, and from wild boars to cattle. In NAq an additional fourth transition rate was identified: from badgers to cattle. However, host transition remained a rare event. Our results suggest that wild boars could be an intermediary host between badgers and cattle in the circulation of the studied strains in CdO and NAq. Our results also highlight the differences between these two areas, suggesting that the transition pattern does not only depend on the host species and other ecological, landscape and anthropic factors are important. Abstract : Using whole genome sequencing of Mycobacterium bovis strains collected in two distinct areas of France with an evolutionary model, we showed that the role of host species in the circulation of the pathogen differed between both areas. While wild boars appeared to play the role of an intermediary between badgers and cattle in both areas, the role of badgers differed. Our results suggest that the transition pattern depends on ecological, landscape, and anthropic factors.